Ultrasonographic thyroid findings suspicious for malignancy. Issue 12 (December 2013) - Azar, Nami; Lance, Craig; Nakamoto, Dean; Michael, Claire; Wasman, Jay; Pantanowitz, Liron
<x xml:space="preserve">Abstract</x> Asymptomatic incidental thyroid nodules (thyroid incidentalomas) are found in up to a third of the adult population. There is notable overlap in the sonographic appearance of benign and malignant thyroid nodules. This paper provides a brief review of the ultrasound findings of thyroid nodules that are suspicious for malignancy with pathologic correlates. We then discuss the standard approach to a fine needle aspiration biopsy of a thyroid nodule at our institution. Finally, we review specific diagnostic challenges in image guided fine needle aspiration biopsies. Diagn. Cytopathol. 2013;41:1107–1114. © 2013 Wiley Periodicals, Inc.